Strategic Reward Management and its Role in Enhancing Employee Performance in Education - Zueva Oksana (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
Reward systems play a central role in shaping employee motivation, satisfaction, and overall organisational performance. This paper examines the impact of financial and non-financial rewards on employee behaviour, with a particular focus on the education sector. Drawing on a wide range of academic literature, the study highlights the importance of aligning reward strategies with organisational goals, culture, and employee expectations. The findings suggest that while financial rewards remain essential for attracting and retaining talent, intrinsic rewards such as recognition, professional development, and work-life balance have a stronger influence on job satisfaction and long-term commitment, especially among academic staff. The paper also explores the relationship between reward systems and turnover, motivation, and performance outcomes. Based on the analysis, practical recommendations are proposed for developing a balanced and effective reward system that enhances both individual and organisational success.